Stachytarpheta atkinsiae, a new species of Verbenaceae endemic to the Chapada Diamantina, Bahia, Brazil - Harley, Raymond M.; Antar, Guilherme Medeiros; Giulietti, Ana Maria (Phytotaxa, 2019)
Stachytarpheta atkinsiae, belonging to the Radlkoferiana group from the Chapada Diamantina, Bahia state Brazil, is here described. It is a red-flowered species, and unusual in being a large, much-branched shrub, with densely lanate indumentum. The species shows similarities with S. froesii and S. radlkoferiana, but differs from both vegetative and floral characters.We provide a full description of the species, together with illustrations, a conservation status assessment, and a distribution map.